Projeto e concepção de motovibrador linear para aplicação em manobras de chaves seccionadoras de alta tensão - Oliveira, Leonardo Castilhos de (2023)
The present research covers the design and conceptual conception of the linear vibrator, responsible for automating the limit switch of electrical contacts in high voltage disconnect switches. With the automation of the system, there was a significant increase in the operating reliability of opening and closing maneuvers in electrical energy substations, thus also achieving high levels of operational safety and a significant reduction of undesirable interruptions in the supply of electrical energy. The research works based on the application of controlled linear vibration in disconnect switches, with the purpose of reducing the frictional forces between the main current-passing contacts, automating the process, which is currently carried out manually. For the project development, the NIOSH methodology and relevant project calculations were used, following the regulatory standards for machinery and equipment. From the theoretical knowledge of the problem to be elucidated, the study proposes to execute the construction of the three-dimensional model of the vibrator in CAD, as well as the manufacture and assembly in full scale for the application of the tests, validating its performance in the laboratory and later in the field. The field test aimed to verify the performance of the linear vibrator in relieving friction between the fixed and moving contacts of the disconnector. The main conclusion was the automation of the limit switch system for electrical contacts in disconnector closing maneuvers, exercising an innovation process within the electrical sector.